2020
DOI: 10.2337/dc20-2219
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose Monitoring in the Intensive Care Unit During the COVID-19 Pandemic

Abstract: OBJECTIVE Real-time continuous glucose monitoring (rtCGM) in critically ill hospitalized patients holds promise; however, real-world data are needed. RESEARCH DESIGN AND METHODS We placed Dexcom G6 CGM on intensive care unit (ICU) patients at Montefiore Medical Center with confirmed coronavirus disease 2019 (COVID-19) infection and glycemic variability. We analyzed inpatient CGM accuracy using point-of-care (POC) glucose–CGM matched pairs and included patients for analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 14 publications
(12 reference statements)
2
79
1
3
Order By: Relevance
“…18 In the hospital, several studies have described how remote monitoring with Share can be used to reduce inpatient hypoglycemia, 19 improve glucose management, 20 and potentially reduce the need for personal protective equipment in the setting of COVID-19. 21,22 This study has several limitations. Data were from users of a single CGM system within the United States, and results might not be generalizable to users of other CGM systems or in other regions.…”
Section: Conclusion/discussionmentioning
confidence: 96%
“…18 In the hospital, several studies have described how remote monitoring with Share can be used to reduce inpatient hypoglycemia, 19 improve glucose management, 20 and potentially reduce the need for personal protective equipment in the setting of COVID-19. 21,22 This study has several limitations. Data were from users of a single CGM system within the United States, and results might not be generalizable to users of other CGM systems or in other regions.…”
Section: Conclusion/discussionmentioning
confidence: 96%
“…The United States Food and Drug Administration issued a policy to expand the availability and capability of noninvasive remote monitoring devices during the pandemic [10]. Previous studies have shown that CGM use might be feasible and reliable in reducing the frequency of point-of-care glucose testing, patient and healthcare worker exposure, and personal protective equipment (PPE) use during the pandemic [3,4]. Although the usefulness of CGM has been reported, the measured glucose levels have been inaccurate because they are often influenced by agents commonly used in critically ill patients, such as severe COVID-19 patients [8].…”
Section: Discussionmentioning
confidence: 99%
“…Constant glucose monitoring can potentially increase the exposure of healthcare workers to COVID-19. To avoid this situation, studies have evaluated and reported the usefulness and safety of continuous glucose monitoring (CGM) systems [3][4][5][6][7]. CGM devices measure glucose in the subcutaneous interstitial fluid; however, this measurement is affected by several factors in critically ill patients [8].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, two series underscored the usefulness of rCGM in the ICU settings. The first study by Agarwal et al involving 11 critically ill patients due to COVID-19 showed that validated real-time continuous glucose monitoring (rtCGM) is a potential addition to the standard point of care (POC) glucose testing as it is feasible, acceptable, and reliable [54].…”
Section: Health-related Technologiesmentioning
confidence: 99%